Vinterplanering i det offentliga rummet : En fallstudie av översiktsplan, planprogram och detaljplan i Luleå kommun - Olsson, Anton (Blekinge Tekniska Högskola, Institutionen för fysisk planering, 2021)
Every day we stay in some form of public space, whether it is the collective laundry room in the basement or during a jog through the park. The public space is something many people today take for granted and they are often planned for large attractive public spaces. Where social interactions take place, physical activity, play and rest. In this work, the design of the public space is problematized according to the climate changes that society and the world will face today. How should the public space be planned to be attractive all year round? Are we really planning the right way today? This master's thesis describes what public space is and how to make it as attractive as possible according to prominent city architects and architects. They want to promote social interactions and make the public space lively around the clock, during each season. After closer examination, it is difficult to apply this planning where the climate is colder than in, for example, Barcelona, Spain. With this as a basis, the work has produced a planning basis for how to plan the public space according to colder climates. The planning documentation is then applied to several different case studies at different planning levels (overview plan, planning program and detailed plan) made in the Swedish city of Luleå. Luleå is located far up in northern Sweden with a cooler climate. What we can see is that the different levels take up different amounts of winter planning depending on how much they can regulate. Some of the documents do not consider the winter planning while some do this in a very good way. Which is interesting because all planning documents in a city with such a cold climate should actively plan for a colder climate. The conclusion is that Luleå municipality applies good winter planning across different planning levels. However, there is development potential to ensure good winter planning.